Study Of Production Verses In Tafsir Al-Jailani - Muhaini, Akhmad; Suwito; Khusnul Khotimah (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
This research is entitled Study of Production Verses in Tafsir Al-Jailani which aims to reveal how Tafsir Al-Jailani understands the verses related to the concept of production in Islamic perspective. The problems studied include tafsir's understanding of the spiritual, ethical, and technical aspects of production, as well as its relevance in building production principles that are just and blessed. This research uses a qualitative method with a literature study approach. Tafsir Al-Jailani is used as the main source, supported by the study of production theory in Islam and other tafsir literature to provide a more comprehensive analysis. The data were analyzed using thematic method to identify the main message of the verses related to production and its contribution to Islamic economic theory. The results show that Tafsir Al-Jailani emphasizes the importance of straight intention, honesty, and hard work in production activities. Production is understood not only as an economic activity, but also an act of worship that must fulfill the principles of justice and sustainability. This interpretation also offers an in-depth view of the importance of paying attention to the balance between worldly and ukhrawi needs in the production process.